Concepções de professores sobre avaliação: estudo de caso de ensino de língua espanhola no CEL de São Carlos - Silveira, Milena Ribeiro (2018)
The main goal of this survey is to evaluate the concepts of spanish language teachers evaluation from Study Language Center from São Carlos SP and to compare with proposals described in National Curricular Plans (NCP Brazil, 1998 and 2000) and National Curricular Orientations (OCE Brazil, 1998) and try to discuss possible trends in their didactic practice evaluations described in our survey context. By the way, we use as data collection tool an interview with CEL coordinator with the aim of understanding the principle of the pedagogical project of CEL and a questionnaire to Spanish teachers with the main of chart the conceptions and practices evaluated from the group. From the analysis, we try to discuss what are the conceptions about concepts of express evaluation by teachers to base their practices and how these conceptions relate to the guidelines and national curricular orientation. Our theoretical foundation is based on authors who discuss evaluation in the general field of education in the general field of education (LIBÂNEO, 1991, PERRENOUD, 1999; SACRISTÁN, 2000, HOFFMAN, 2002; LUCKESI, 2011) and in the field of applied linguistics (SCARAMUCCI, 2004, LEFFA, 1998, VIEIRA-ABRAÃO, 2012). Keyword: Evaluate, Study Language Center, Spanish Language.